Highly efficient cellular cloning using Ferro-core Micropallet Arrays. Issue 1 (December 2017) - Westerhof, Trisha; Cox-Muranami, Wesley; Li, Guann-Pyng; Bachman, Mark; Fan, Hung; Nelson, Edward
Abstract Advancing knowledge of biological mechanisms has come to depend upon genetic manipulation of cells and organisms, relying upon cellular cloning methods that remain unchanged for decades, are labor and time intensive, often taking many months to come to fruition. Thus, there is a pressing need for more efficient processes. We have adapted a newly developed micropallet array platform, termed the "ferro-core micropallet array", to dramatically improve and accelerate the process of isolating clonal populations of adherent cells from heterogeneous mixtures retaining the flexibility of employing a wide range of cytometric parameters for identifying colonies and cells of interest. Using transfected (retroviral oncogene or fluorescent reporter construct) rat 208 F cells, we demonstrated the capacity to isolate and expand pure populations of genetically manipulated cells via laser release and magnetic recovery of single micropallets carrying adherent microcolonies derived from single cells. This platform can be broadly applied to biological research, across the spectrum of molecular biology to cellular biology, involving fields such as cancer, developmental, and stem cell biology. The ferro-core micropallet array platform provides significant advantages over alternative sorting and cloning methods by eliminating the necessity for repetitive purification steps and increasing throughput by dramatically shortening the time to obtain clonally expanded cell colonies.